2018
DOI: 10.1016/j.ultsonch.2017.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound impact on whey protein concentrate-pectin complexes and in the O/W emulsions with low oil soybean content stabilization

Abstract: Consumers' preference for products with reduced levels of fat increased in the last years. Proteins and polysaccharides have an important role due to their functional and interaction properties because, when combined in ratios and pH of higher potential for electrostatic interactions they may act as emulsifiers or stabilizers. This study evaluated the ultrasound impact on the electrostatic interaction between pectin (PEC) and whey protein concentrate (WPC) at different WPC:PEC ratios (1:1 to 5:1), and its effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
36
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(46 citation statements)
references
References 48 publications
8
36
0
2
Order By: Relevance
“…In addition, a certain amount of SBP that was distributed in the continuous phase and was crosslinked resulted in an increase in viscosity. This process was also confirmed by Albano and Nicoletti (2018), who showed that oil droplets were coated by the protein and entrapped by the pectin, which formed a network in the continuous phase, stabilizing the system [ 27 ]. Perrechil and Cunha evaluated confocal laser micrographs of emulsions and found that the protein remained around the oil droplets, while the excess protein was homogeneously distributed in the continuous phase [ 28 ].…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…In addition, a certain amount of SBP that was distributed in the continuous phase and was crosslinked resulted in an increase in viscosity. This process was also confirmed by Albano and Nicoletti (2018), who showed that oil droplets were coated by the protein and entrapped by the pectin, which formed a network in the continuous phase, stabilizing the system [ 27 ]. Perrechil and Cunha evaluated confocal laser micrographs of emulsions and found that the protein remained around the oil droplets, while the excess protein was homogeneously distributed in the continuous phase [ 28 ].…”
Section: Resultssupporting
confidence: 52%
“…The green and red fluorescence modes were used to produce excitation wavelengths of 488 and 543 nm, respectively. Images were obtained from the 2 channels and then superimposed [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…according to formula (16), it was found that the relationship between αβ and E 0 /S 0 was linear, and the results of origin were used to fit the results in Table 2, and the results are shown in Figure 7b. As shown in Figure 7b, there was a linear relationship between the kinetic parameters αβ and E 0 /S 0 values.…”
Section: Calculation Of Kinetic Constantsmentioning
confidence: 99%
“…[15] Many researchers used HIU, which use acoustic frequencies between 20 and 100 kHz, to alter the molecular characteristics in order to get much better functional properties of food protein. Albano and Nicoletti [16] reported that the ultrasound can increase emulsion stability due to the increase in apparent viscosity caused by droplet size reduction and consequent increase of interfacial area. They found that the ultrasound reduced the suspension viscosity and the size of the biopolymer complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound can enhance the functional properties of biopolymers, producing stable emulsions with little requirement for surfactants (Kaltsa, Michon, Yanniotis, & Mandala, 2013). Albano and Nicoletti (2018) successfully improved the stability of a whey protein concentrate-pectin emulsion using ultrasound. Similarly, Sui et al (2017) demonstrated that the emulsifying activity index and emulsion stability index of an emulsion system stabilized with soybean protein isolate and lecithin increased after ultrasound treatment.…”
Section: Accepted Manuscriptmentioning
confidence: 99%